Pan-Bcl-2 inhibitor Obatoclax is a potent late stage autophagy inhibitor in colorectal cancer cells independent of canonical autophagy signaling - Köhler, Bruno Christian; Jassowicz, Adam; Scherr, Anna-Lena; Lorenz, Stephan; Radhakrishnan, Praveen; Kautz, Nicole; Elßner, Christin; Weiß, Johanna; Jäger, Dirk; Schneider, Martin; Schulze-Bergkamen, Henning (BMC cancer, 2015)
Colorectal cancer is the third most common malignancy in humans and novel therapeutic approaches are urgently needed. Autophagy is an evolutionarily highly conserved cellular process by which cells collect unnecessary organelles or misfolded proteins and subsequently degrade them in vesicular structures in order to refuel cells with energy. Dysregulation of the complex autophagy signaling network has been shown to contribute to the onset and progression of cancer in various models. The Bcl-2 family of proteins comprises central regulators of apoptosis signaling and has been linked to processes involved in autophagy. The antiapoptotic members of the Bcl-2 family of proteins have been identified as promising anticancer drug targets and small molecules inhibiting those proteins are in clinical trials.